2018
DOI: 10.1073/pnas.1806513115
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-dependent recruitment of the yeast NuA4 acetyltransferase complex by MRX at DNA breaks regulates RPA dynamics during resection

Abstract: The KAT5 (Tip60/Esa1) histone acetyltransferase is part of NuA4, a large multifunctional complex highly conserved from yeast to mammals that targets lysines on H4 and H2A (X/Z) tails for acetylation. It is essential for cell viability, being a key regulator of gene expression, cell proliferation, and stem cell renewal and an important factor for genome stability. The NuA4 complex is directly recruited near DNA double-strand breaks (DSBs) to facilitate repair, in part through local chromatin modification and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(82 citation statements)
references
References 49 publications
9
73
0
Order By: Relevance
“…NuA4 has been shown to play an important role for the recruitment of chromatin remodelers such as INO80, SWI/SNF and RSC to DNA repair sites (Bennett & Peterson, 2015;Downs et al, 2004;House et al, 2014). Our recent work indicates that NuA4 is rapidly recruited to a DSB by the MRX complex (Mre11-Rad50-Xrs2) and this is most likely through a DNA damageinduced phospho-dependent interaction with the Xrs2 protein (Cheng et al, 2018). In addition, we have shown that NuA4 directly acetylates RPA to modulates its dynamic association with ssDNA during the repair process (Cheng et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…NuA4 has been shown to play an important role for the recruitment of chromatin remodelers such as INO80, SWI/SNF and RSC to DNA repair sites (Bennett & Peterson, 2015;Downs et al, 2004;House et al, 2014). Our recent work indicates that NuA4 is rapidly recruited to a DSB by the MRX complex (Mre11-Rad50-Xrs2) and this is most likely through a DNA damageinduced phospho-dependent interaction with the Xrs2 protein (Cheng et al, 2018). In addition, we have shown that NuA4 directly acetylates RPA to modulates its dynamic association with ssDNA during the repair process (Cheng et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…Acetylation of other proteins, such as p53 (69), Gata-1 (70), and Stat3 (71), all serve as examples of proteins displaying increased binding affinities for specific DNA substrates when acetylated. Interestingly, acetylation of replication protein A (RPA) promotes its displacement from ssDNA during DSB repair (72), and acetylated FEN1 displays lower substrate binding affinity (63). All of these proteins are hypothesized to undergo conformational changes upon acetylation, which may alter their ability to interact with and bind to their cognate substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, acetylation of replication protein A (RPA) promotes its displacement from ssDNA during DSB repair [72], and acetylated FEN1 displays lower substrate binding affinity [63]. All of these proteins are hypothesized to undergo conformational changes upon acetylation, which may alter their ability to interact with and bind to their cognate substrates.…”
Section: Discussionmentioning
confidence: 99%